Synthesis of Tetracyclic Phenazine Derivatives by Reactions of Lawsone with Diamines - Jain, R.; Agarwal, O.P.; Jain, S.C. (Asian Journal of Chemistry, 2012)
The reaction of lawsone (1) with 1,2-diaminobenzene (2) gave the tetracyclic phenazine derivatives (4) while with 2,3-diaminotoluene (5) a mixture of the phenazine regioisomers (8) and (9) were obtained, on simple grinding as also on heating. No reaction was observed with 1,2-diaminoethane (10) under similar conditions.